The Use of Ethnomedicinal Plants by the People of Bharat Pokhari, Kaski (Prithvi Journal of Research and Innovation, 2021)
Ethnomedicine is the study of traditional uses of plant by people who live in rural areas. The present study is the documentation of traditional knowledge on plant utilization by local people in Bharat Pokhari, Kaski and was conducted during February-July 2020 by using the following methods. Data about medicinal uses of plants were collected using the questionnaire, personal interview and group discussion. Voucher specimens were collected from informants and identified with the help of available literature and taxonomic experts. The plant species were then categorized based on their medicinal uses. During the study, 56 medicinal plant species belonging to 36 families were documented. These plants have been used to treat various diseases. The highest number of species (20) being used for gastro-intestinal disorders, followed by bone and muscular ailments (13), cold and cough (11) and respiratory system ailments (10). In the study area, the popularly used medicinal plant species are Acacia pennata Willd, Acorus calamus L., Aloe vera (L.) Burm.f., Azadirachta indica A. Juss., Cassia fistula L., Centella asiatica (L.) Urb., Ocimum sanctum L., Terminalia chebula Retz., and Viscum album L.